Iron supplementation: What is it? How to use it to overcome iron deficiency. - Hill, R. (2000)
One of the more common problems that occurs with elite level athletes, especially females, involves an excessive loss of iron from training and an inadequate intake of iron in their diets resulting in something called "iron deficiency" and at the extreme level "anaemia". Although iron supplementation in excess of normal iron stores does not enhance performance, a decrease of the iron stores has been found to decrease an athletes performance. Iron deficiency affects performance in two ways [9]. If iron stores are low, then haemoglobin (Hb) production will be negatively affected. Haemoglobin is one of the primary transport mechanisms for oxygen to move throughout the body and is located inside red blood cells (RBCs). If Hb production is limited or reduced this will negatively impact peak oxygen uptake and reduce the delivery of oxygen to the working muscles. Secondly, reduced iron decreases the ability of the muscles to use oxygen for the chemical production of energy (via the formation of ATP), thus aerobic exercise can be impaired. An iron deficiency not only can affect competitive performance, but it may also affect training. Iron deficiency may reduce the ability of the athlete to train in the right intensity zones. Thus, the training process may be impaired and the resulting adaptation will also be negatively impacted. This review will give a brief introduction of the role iron plays in the production of RBCs and Hb as well as other important chemical energy reactions in the body. Then the paper will define the different stages of iron deficiency, how iron is lost from the body, and the more practical methods for replacing iron to he lp maintain athletic performance. Why is iron important with regard to performance? Iron plays an essential role in the body because: 1. It is essential for the production of oxygen transport proteins, Hb in the blood and myoglobin in the muscle; 2. It is a component of erythropoiesis (production of new RBCs); 3. It is a component in the electron transport system that controls the release of energy from the cells (using about 2% of iron stores). Unfortunately, the body does not manufacture it`s own supply of iron and thus, the athlete must rely on their diet for their iron source. The body contains about 3-4 grams of iron at any one time. The largest component of iron in the body is found in Hb (60-70% or total iron) and myoglobin in the muscle tissues (10% of total iron) [17]. About 30% of the body`s total iron in a healthy young adult male (and about 10% in females) is stored in the form of ferritin (known as storage iron) located in such areas as the liver, bone marrow, and muscle. From these locations, iron is transported through the body via the blood by transferrin. Table 1 depicts a typical range of these substances for adult females. However, it must be understood that each laboratory establishes their own normal range based on the general population in their immediate geographic area and these values can vary from lab to lab due to this fact.